Diseño de un plan de mejoramiento integral para la empresa de servicios “El Café de la Vaca”, ubicada en la provincia de Pichincha. - Moscoso Orellana, Sonia Carolina (2013)
This proposal is intended to help improve the corporate image wherein the improvement of key processes are there in "The Cow Cafe" ensure their effectiveness, such as customer service both internal and external also to add value and make better use of the resources used for the development of processes, resulting in a quicker response time to their customers leading to satisfaction with the service and product you are buying. Comprehensive Improvement Plan will contribute to customer satisfaction, which leads to loyalty from them by implementing customer service policies, expansion of markets, and develop continuous improvement policies and troubleshooting.